The association between social capital and loneliness in different age groups: a population-based study in Western Finland - Fredrica Nyqvist; Christina R. Victor; Anna K. Forsman; Mima Cattan (BMC, 2016)
Abstract Background Previous studies of loneliness have largely focused on establishing risk factors in specific age groups such as in later life or in young people. Researchers have paid less attention to the link between social capital and loneliness across different age groups. The aim of this study was to examine the association between social capital and experienced loneliness in different age groups in a Finnish setting. Methods The data originates from a population-based cross-sectional survey conducted among 4618 people aged 15-80 in Western Finland in 2011. The response rate was 46.2 %. The association between social capital, measured by frequency of social contacts, participation in organisational activities, trust and sense of belonging to the neighbourhood and loneliness was tested by logistic regression analyses stratified by four age groups. Results Frequent loneliness (defined as experienced often or sometimes) was higher among younger people (39.5 %) compared to older people (27.3 %). Low levels of trust were linked to loneliness in all four age groups. The association between other aspects of social capital and loneliness varied across age groups. Conclusions Frequent loneliness is common among the general adult population and could be seen as a public health issue. Our findings imply that low social capital, especially in terms of low trust, may be a risk factor for loneliness. However, further research is needed to assess the influence of poor health and reverse causality as explanations for the findings.